2019
DOI: 10.1109/access.2019.2902372
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning for Position-Aided Millimeter Wave Beam Training

Abstract: Accurate beam alignment is essential for beambased millimeter wave communications. Conventional beam sweeping solutions often have large overhead, which is unacceptable for mobile applications like vehicle-to-everything. Learningbased solutions that leverage sensor data like position to identify good beam directions are one approach to reduce the overhead. Most existing solutions, though, are supervised-learning where the training data is collected beforehand. In this paper, we use a multi-armed bandit framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 37 publications
0
108
0
Order By: Relevance
“…Remark 4. When the Nakagami parameter m = 1, namely Rayleigh fading channel, then the equality holds in (39).…”
Section: ) Coverage Probability For the Uplink Phasementioning
confidence: 99%
“…Remark 4. When the Nakagami parameter m = 1, namely Rayleigh fading channel, then the equality holds in (39).…”
Section: ) Coverage Probability For the Uplink Phasementioning
confidence: 99%
“…15, it is confirmed that our proposed solution tracks near the best beam pair quite well even in a practical fast time-varying channel with a far-less sounding overhead. As a demonstration, rather than relying on simulations under a geometric statistical channel model, we adopt a raytracing tool to show that our proposed solution performs well under more realistic time-varying channel parameters (angles, powers, and relative delays) for a moving MS scenario in a specific site, such as trends in [11], [12], [72], [73]. In Fig.…”
Section: B Lower Sounding Overhead Beam Trackingmentioning
confidence: 99%
“…The authors of [8] use a UCB-based policy for beam-alignment in high speed train applications. The work in [9] introduces a position-aided mmWave beam selection technique. The more recent work [10] also uses the contextual stochastic bandits with a prior knowledge on the channel fluctuations to reduce the beam-alignment delay.…”
Section: Introductionmentioning
confidence: 99%